Effective communication and sharing information at clinical handovers - Radka Pokojová; Sylva Bártlová (University of Ostrava, 2018)
Aim: The aim of this study was to present an overview of current knowledge of approaches to improving patient safety and to ensuring continuity of care at clinical information handovers (handoffs). Design: Descriptive summarizing study. Methods: PubMed, Science Direct, Embase and Google Scholar databases were studied, focusing on papers published in English over the past five years. The overview included papers dealing with the effectiveness of patient information transfer between members of staff, teams, and healthcare providers. After classification of materials, 28 articles were finally analyzed. Results: The tools for information handovers were mostly (i.e., in 18 instances) based on the mnemonic SBAR list. To a lesser extent, IPASS technology, the structure of body systems, and a checklist for trauma patients were used. The quality of transferred information was most frequently assessed at ICUs. Conclusion: The implementation of structured approaches for both oral and written information on patients is problematic, but the authors agree that it is necessary to take into account the particular conditions and context of communication.